Construction on wood in the south of Chile. The history of a cultural tradition and the heritage recovery applied on a case: House Prochelle I - Muñoz LeBreton, Susana (2018)
This investigation is framed on a bibliographical research about the heritage architecture of the Región de los Ríos, a valorization project, organized by the Dirección de Arquitectura of the Ministerio de Obras Públicas, which had as its final objective the compilation and charting of all the elements of tangible and intangible heritage content, related to the territory, during the years 2009 -2010. Part of this investigation gives light on a sequence of associative events, also called cultural heritage, on the historical construction in the south of Chile, and which in general it is dissociated with the other cultural groups which occupied the territory, Mapuche-Williche, Spanish and German.This research intends to give lights on this multicultural evolution of architecture, based on an specific ecosystem and adapted to a terrestrial dynamic such as earthquakes and tsunamis. This process ends with the declaration of this house as a National Historical Monument under the category of construction on wood. One must emphasize that the lignea architecture is part of a constructive tradition of forty thousand years of evolution, and which today, at the beginning of the XXI century, it is going through an accelerated process of extinction.